» Cette reine qui fait une si piètre figure « Maria von Medici in der europäischen Geschichtsschreibung des 19. Jahrhunderts - Régerat-Kobitzsch, Miriam (Pariser Historische Studien, 2020)
Successive generations have remembered Marie de' Medici (1575-1642), Queen of France, as an incompetent regent, obsessed with power and alleged to have murdered her husband. Moreover, historians often saw no more to her cultural work and politics than a female and Italian parenthesis between the reign of Henry IV and the ministry of Richelieu. This unfavourable image of the second Medici-regent survived the French Revolution and was solidified in the master narrative of an increasingly bourgeois, republican and secular French nation. The present volume provides the first-ever investigation into Marie de' Medici's colourful reception during the 19th century. It offers an in-depth analysis of historical writing, society and politics in the pan-European period of crisis and change called the Age of Nationalism